Effects of Ultraviolet Radiation on the Properties of Wood Plastic Composite with Recycled Polypropylene Matrix - Cahyo Budiyantoro; Muhammad Ikbar Fawwas Ghazy; Bastian Bilyferdin (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2025)
Indonesia has an abundance of wood sawdust waste and polypropylene (PP) plastic waste, which remain underutilized. This study aims to investigate the effects of ultraviolet (UV) radiation on the mechanical and physical properties of wood plastic composite (WPC) made from recycled polypropylene. WPC specimens were fabricated using injection molding with 40-mesh pine and teak wood particles at 10% weight fraction. The samples were exposed to UV radiation for 0, 240, and 750 hours, respectively. Mechanical properties were assessed through impact toughness using the Izod test, while physical properties were evaluated based on density and thickness swelling. The results indicated that prolonged UV exposure significantly reduced the impact strength and density of WPC while increasing its thickness swelling. Notably, teak-based WPC exhibited greater resistance to UV degradation compared to pine-based WPC. These findings highlight the importance of UV stability in WPC applications for outdoor environments and suggest potential improvements through material modifications or protective coatings.